Synthesis of diverse β-quaternary ketones via palladium-catalyzed asymmetric conjugate addition of arylboronic acids to cyclic enones. Issue 35 (2nd September 2015) - Holder, Jeffrey C.; Goodman, Emmett D.; Kikushima, Kotaro; Gatti, Michele; Marziale, Alexander N.; Stoltz, Brian M.
Abstract: The development and optimization of a palladium-catalyzed asymmetric conjugate addition of arylboronic acids to cyclic enone conjugate acceptors is described. These reactions employ air-stable and readily-available reagents in an operationally simple and robust transformation that yields β-quaternary ketones in high yields and enantioselectivities. Notably, the reaction itself is highly tolerant of atmospheric oxygen and moisture and therefore does not require the use of dry or deoxygenated solvents, specially purified reagents, or an inert atmosphere. The ring size and β-substituent of the enone are highly variable, and a wide variety of β-quaternary ketones can be synthesized. More recently, the use of NH4 PF6 has further expanded the substrate scope to include heteroatom-containing arylboronic acids and β-acyl enone substrates. Graphical abstract: